Analysis of gaharu essential oil GC/GCMS - Shahrizal, Ramli (2006)
In this study, 7 samples of Gaharu essential oil from the industries was analyzed using Gas Chromatography/ Gas Chromatography Mass Spectrometry (GC/GCMS). All the 7 samples (G1, G2, G3, SP001, SP002, SP003 and SP004) was identified and analyzed to determine the best quality of Gaharu essential oil. Difference grade of Gaharu contain different percent and different compounds in the essential oil. The best quality of Gaharu essential oil is depends on the important chemical components that contribute to the special characteristic of aroma to Gaharu and the number of components exists in all samples. Agarospirol, jingkoh eremol and kusenol are the important compounds that contribute the characteristic of aroma to Gaharu. Every single oil normally has more than a hundred components and it can be detected through analyzing the essential oil with a chromatograph. The samples will be analyzed by GC/MS equipment. GC/MS equipment have been choose to analyze the chemical components in Gaharu essential oil because this equipment make an effective combination for chemical analysis. The result of this study, sample Gaharu essential oil, G1 is the best quality of essential oil recommended by industry in Malaysia.